Ownership, Authority, and Self-Determination - Hendrix, Burke A. (Penn State University Press, 2025)
Much controversy has existed over the claims of Native Americans and other indigenous peoples that they have a right—based on original occupancy of land, historical transfers of sovereignty, and principles of self-determination—to a political status separate from the states in which they now find themselves embedded. How valid are these claims on moral grounds? Burke Hendrix tackles these thorny questions in this book. Rather than focusing on the legal and constitutional status of indigenous nations within the states now ruling them, he starts at a more basic level, interrogating fundamental justifications for political authority itself. He shows that historical claims of land ownership and prior sovereignty cannot provide a sufficient basis for challenging the authority of existing states, but that our natural moral duties to aid other persons in danger can justify rights to political separation from states that fail to protect their citizens as they should. Actual attempts at political separation must be carefully managed through well-defined procedural mechanisms, however, to foster extensive democratic deliberation about the nature of the political changes at stake. Using such procedures, Hendrix argues, indigenous peoples should be able to withdraw politically from the states currently ruling them, even to the point of choosing full independence.